حاجات الدارسين الماليزيين الكبار في تعلم اللغة العربية بوصفها لغة أجنبية :b - موهيندو، فيصل مسعود (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2010)
The study aims at investigating the linguistic needs of Malaysian adults and finding out how the Arabic teaching centres' curriculum caters for these needs. The three centres are: Institute for language advancement, International Islamic University Malaysia, Bayana Islamic centre for teaching Arabic, University of Malaya, and Al Diwan Arabic centre, Kuala Lumpur. The study begins with the situation of Arabic in Malaysia, it outlined the factors affected the spread of Arabic language in Malaysia, and the aims of teaching. In chapter two, the researcher defined the meaning of the Arabic curriculum for teaching Arabic language, its components, objectives, types and levels. In chapter three the study indicated on the topic of the psychology of the adults in terms of their ages, nature, culture, their perception, attitudes towards learning, and the teachers' perception towards the needs of adults and teaching. Then the researcher distributed questionnaires to both learners and teachers in three centres of teaching Arabic language, then analysed the data and ended with the conclusion, recommendation and references.